Physicians’ and Pharmacists’ Knowledge, Thoughts, and Attitudes of Homeopathy: A Comparative Survey in Türkiye - Egeli Yilmaz D.; GÖKKAYA İ.; RENDA G.; KARTAL M. (My University, 2025)
Abstract Background: Homeopathy, included in traditional and complementary medicine (TCM), is defined as a complementary treatment that aims to improve health through personalized therapy. Physicians and pharmacists play a crucial role in the practice of homeopathy and the delivery of homeopathic medicinal products to the public in Türkiye. This study aimed to evaluate the knowledge, thoughts, and attitudes of physicians and pharmacists on homeopathy in accordance with Turkish regulations. Methods: This descriptive study was carried out on physicians and pharmacists via a web-based questionnaire method. The survey form includes three sections and twenty-three questions. Participants received the survey form via Facebook, Instagram, X (Twitter), and LinkedIn. A total of 475 questionnaires that met the data quality criteria were included in the study. The analysis of the data was performed with the SPSS 23.0 statistical program, with a statistical significance level set at p < 0.05. Results: The study population included 70.3% (n = 334) pharmacists and 29.7% (n = 141) physicians. The study’s results demonstrate that 86.5% of participants had heard of the concept of homeopathy. It was found that a higher rate of hearing about homeopathy was associated with being a pharmacist (OR: 31.5, p = 0.000) and having 10 years or more of professional experience (OR: 7.274, p = 0.000). The participants had correct knowledge about the definition and basic principles of homeopathy. The respondents lacked knowledge on certain aspects of the regulation of homeopathic practice in Türkiye. The primary source of information for pharmacists was undergraduate courses (n = 185, 58.2%), but for physicians, it was social media/television (n = 41, 50.0%). Of the participants, 70.1% (n = 288) thought that homeopathy needs to be incorporated into the undergraduate curriculum, and 91.7% of participants thought that further scientific research on homeopathy is required. Conclusion: Homeopathy courses should be integrated into undergraduate education to improve the awareness of healthcare professionals. Furthermore, the organization of seminars and training courses would enhance their knowledge of the relevant subject.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Entegre ve Tamamlayıcı Tıp; Klinik Tıp (Med); Klinik Tıp; Integrative & Complementary Medicine; Clinical Medicine (Med); Clinical Medicine; Tamamlayıcı ve Alternatif Tıp; Complementary and Alternative Medicine; Apotheker:innen; Homeopathy; Homéopathie; Homöopathie; Médecine traditionnelle et complémentaire; Médecins; Pharmaciens; Pharmacists; Physicians; Traditional and complementary medicine; Traditionelle und komplementäre Medizin; Türkei; Türkiye; Ärzt:innen